Upaya Meningkatkan Hasil Belajar Peserta Didik melalui Penerapan Model Kooperatif Tipe The Power Of Two Berbasis Alat Peraga di Kelas VII SMP Yapis Manokwari - Irmansyah Karoror; Sri Wahyu Widyaningsih; Sri Rosepda Br. Sebayang; Irfan Yusuf (LP4MK STKIP PGRI Lubuklinggau, 2020)
This study aims to determine how the application of the power of two type of cooperative learning model based on teaching aids to improve student learning outcomes in class VII A SMP YAPIS Manokwari. The instrument used was a learning achievement test to measure cognitive aspects and observation of students' activities in practicum to measure psychomotor aspects. This research is included in Classroom Action Research (CAR). Instrument analysis uses CVR and CVI to see the validity and reliability. Analysis of cognitive results using Microsoft Excel and psychomotor results using the Rasch Model. The results of this study indicate that, in the first cycle of classical completeness in the cognitive aspects by 65%, and psychomotor aspects by 84%. In second cycle of classical completeness in the cognitive aspects of 81%, and psychomotor aspects by 90%. This shows that learning using the power of two cooperative model based on teaching aids can improve student learning outcomes.